Medical Waste Disposal and Occupational Health Hazards in Dental Clinics in Nablus Districts - Salem Adli Mahmoud Mosleh (My University, 2004)
The present study aimed at identifying dental waste techniques and the most common occupational health hazards at dental clinics in Nablus district. Out of a total of 134, dentists working at private and NGO’s clinics, 97 were included in this study, 92.6% were males. A specially designed questionnaire was used. Collected data were then analyzed using SPSS. With regard to waste disposal, this study showed that the majority of the surveyed clinics dispose medical waste into general trash (amalgam, 62.9%; sharps, 61.9%). This study showed that 54.6% wear gloves during treatment of patient's, 48.5%, wearing gloves during amalgam fillings, 36.8% wearing masks and 15.8% wearing eye protection. HBV vaccination was reported by 74.2%. Stress (37.1%) and headaches (48.4%) were found to be the most common occupational health problems. Sterilization methods still depend on dry heat methods (83.2%) which, proven to be inefficient as it applied in most clinics. The use of 70% alcohol solutions as a disinfectant agent by 53.6% is another indication of lack of either knowledge or ignorance by working clinics. In conclusion, it seems that there is an urgent need for intervention in order to promote awareness of occupational health hazards and their control measures.

هدفت هذه الدراسة إلى التعرف على واقع أطباء الأسنان في محافظة نابلس من حيث تدابير التخلص من النفايات الطبية الطرق الوقائية من العدوى والأمراض الناجمة عن الممارسات الطبية. تكونت عينة هذه الدراسة من 97 طبيب أسنان من أصل 134 يعملون في عيادات خاصة وأهلية وحكومية في محافظة نابلس حيث كانت نسبة الذكور 92.6%. تم جمع المعلومات باستبانة صممت لهذا الغرض ومن ثم تم تحليل المعلومات باستخدام الرزمة الاحصائية SPSS. فيما يتعلق بطرق التخلص من النفايات الطبية، بينت هذه الدراسة ان غالبية العيادات من عينة الدراسة تعمل على التخلص من نفاياتها عن طريق سلة المهملات (بقايا الحشوات 62.9%، الادوات الحادة 61.9%). وقد بينت نتائج الدراسة كذلك أن 45.6% من أطباء الأسنان يستعملوا دائماً القفازات خلال ممارستهم لعملهم، منهم 48.5% يستعملوا القفازات أثناء عمل حشوات الأملغم، و36.8% دائماً يضعون الأقنعة الواقية، و15.8% دائماً يضعون النظارات أثناء المعالجة و 74.2% طعموا ضد التهاب الكبد الوبائي نوع ب. كما تبين ان كما تبين أن ما نسبته 37.1% من أطباء الأسنان يشكون في كثيرا من الاحيان من التوتر و أن ما نسبته 48.4% يشكون من الصداع. اما فيما يتعلق بوسائل التعقيم المتبعة فقد تببن ان ما نسبته 83.2% منهم يستعملوا جهاز التعقيم الحراري الجاف و ان 53.6% يستعملوا الكحول كمادة معقمة. ان مثل هذه الممارسات لدليل واضح على المعرفة المحدودة او الاهمال في اتباع المعايير السليمة والمتبعة في هذا المجال. وأخيراً فقد تبين أن طرق التخلص من النفايات الطبية السنية وطرق التعقيم والإجراءات الوقائية وغيرها من السلامة المهنية والصحية المتبعة في معظم عيادات الأسنان في محافظة نابلس لم تكن بالقدر الكافي والفعال لذا لا بد من التدخل السريع من قبل الجهات المعنية بهدف زيادة الوعي الصحي والسلامة المهنية في عيادات طب الاسنان.
إدارة النفايات الطبية والسلامة المهنية في عيادات طب الأسنان في محافظة نابلس